A25 ASSOCIATION OF BIOLOGIC PRESCRIBING FOR INFLAMMATORY BOWEL DISEASE WITH INDUSTRY PAYMENTS TO PHYSICIANS - Khan, R (J Can Assoc Gastroenterol, 2019)
BACKGROUND: Financial conflicts of interest (FCOIs) between the pharmaceutical industry and physicians have been associated with changes in prescribing behaviour, though the nature of this association in inflammatory bowel disease (IBD) is unknown. AIMS: To investigate the relationship between the prescribing of biologic medications for IBD and industry payments to physicians from pharmaceutical companies making those medications. METHODS: We used two US databases from 2013–2015: (1) The Centres for Medicare and Medicaid Services (CMS) Part D prescription claims database, which documents medications prescribed under Medicare; and (2) Dollars for Docs, which lists payments made by pharmaceutical companies to physicians. We identified physicians who prescribed biolgic medications for IBD and recorded industry payments physicians received from companies producing biologic medications in three categories: (1) Education; (2) Food and travel; and (3) other, such as speakers and consulting fees. A linear regression tested the association between payments received by a physician and dollar value of prescriptions written for biologics. A second regression was performed with an additional predictor variable to account for patient volume. RESULTS: 3475 gastroenterologists prescribed IBD biologics from 2013–2015. 3441 (99.0%) received at least one payment from a company producing the biologic medications they prescribed (Table 1). There was a significant association between the prescribing of biologics and the receipt of payments from companies making biologics (p<0.001; R(2)=6.49% ). For every $1000 in industry payments, there was an associated $2441 increase in prescription claims (95% CI: $2133 to $2748) (Figure 1). When accounting for patient volume, the associated prescription cost was significantly related to the value of industry payments (p<0.001, R(2)=7.64%). For every $1000 in industry payments, there was an associated $3846 increase in prescription claims (95% CI: $3285 to $4407). The strength of the association was similar for all three types of payments. CONCLUSIONS: There is an association between the receipt of industry payments from pharmaceutical companies making biologics for IBD, and the prescribing of those medications. These results highlight a potentially concerning influence of industry on prescribing behaviour. FUNDING AGENCIES: None